Circumcision with a novel disposable device in Chinese children: A randomized controlled trial. (13th September 2012) - Pan, Feng; Pan, Lianjun; Zhang, Aixia; Liu, Yong; Zhang, Fenglei; Dai, Yutian
<x xml:space="preserve">Abstract</x> Objectives To compare the outcomes and complications of three methods of circumcision in a Chinese pediatric population. Methods A total of 120 children were randomly assigned to three groups. Group I was submitted to circumcision using the Shenghuan disposable device according to Yan's method; group II was submitted to circumcision using the same device, but according to Peng's methods; group III was operated on by using the conventional scalpel/suture technique. The three groups were compared mainly by the following outcomes: duration of surgery, intraoperative bleeding, postoperative pain, cosmetic effect, and the rates of edema, dehiscence, scarring, adhesion and infection. Results Groups I and II had less intraoperative bleeding. In terms of the duration of surgery, group I was the quickest. Pain scores in using the Shenghuan disposable device were higher at 6 h after surgery compared with the conventional scalpel/suture technique. The percentage of patients using paracetamol in group II was higher than that in group III at 12 h after surgery. Other complications were similar, and all three groups had successful outcomes. Conclusions Circumcision using the Shenghuan disposable device represents a safer and time‐saving option compared with the conventional scalpel/suture technique, with better cosmetic outcomes. Yan's method seems to be better than Peng's method when using the Shenghuan disposable device for circumcision in children.